Answer: 72 Step-by-step explanation: Substitute c = 5 into h(c) , that is h(5) = 6(5)² – 76 – 2 = 6(25) – 78 = 150 – 78 = 72 Log in to Reply

Plug in five to the equation, for example: h(5)=6(5) squared -76-2 5 squared is 25 6×25=150 … 150-76-2=72…. h(5)=72 divid both sides by 5 to find the value of “h” (h=14.4) Log in to Reply

Answer:72

Step-by-step explanation:Substitute c = 5 into h(c) , that is

h(5) = 6(5)² – 76 – 2 = 6(25) – 78 = 150 – 78 = 72

Plug in five to the equation, for example: h(5)=6(5) squared -76-2 5 squared is 25 6×25=150 … 150-76-2=72…. h(5)=72 divid both sides by 5 to find the value of “h” (h=14.4)